Justifying the Need for Smoothing Tools by Islamic Banks - Khan, Mohammad Bilal; Conteh, Seedy; Ghafoorzai, Shaiq Ahmad; Mohtashem, Mohammed Meeran Jasir; Hai, Abdul (El-Barka, 2021)
This paper focuses on the positive impacts of using smoothing tools such as Profit Equalisation Reserve or PER and Investment Risk Reserve or IRR to smoothen the rate of return or profit on investments to investment account holders (IAH) of Islamic financial institutions (IFIs). Since the goal of introducing PER and IRR into Islamic banks is to compete with the conventional banking industry, it is a shield used by Islamic banks to protect their risks such as displaced commercial risk (DCR), withdrawal risk (WR), and reputation risk. This is a qualitative review of the positive impacts of using smoothing tools in Islamic financial institutions. One of the major issues highlighted is Islamic banks' sensitivity to the conventional interest rate changes because many Islamic banking products are benchmarked against the conventional interest rate. Moreover, the limited techniques and instruments available to mitigate the rate of return risk also need the regulators' serious attention. Before the use of smoothing tools was restricted by BNM, Islamic banks were allowed to save up until 15% from profit gain. However, in certain circumstances, BNM has allowed IB’s to save up to 30% from profit gains. Hence, smoothing tools like PER and IRR enabled Islamic banks to be competitive and manage their unique risks. This research is focused on the positive aspects of using smoothing tools (STs) and does not cover the negative aspects from the Shari’ah, legal or corporate governance point of view. Since the abandonment of smoothing tools by IFI’s after the instructions of Bank Negara Malaysia (BNM) in 2014, there has not been much debate about the benefits of using STs. Therefore, this paper might provide a spark required to re-ignite the whole debate once again. Penelitian ini berfokus pada dampak positif dari penggunaan alat pemulusan seperti Profit Equalization Reserve (PER) dan Investment Risk Reserve (IRR) untuk memperlancar tingkat pengembalian atau keuntungan investasi kepada investment account holders (IAH) dari Islamic financial institutions (IFIs). Karena tujuan memperkenalkan PER dan IRR ke bank syariah adalah untuk bersaing dengan industri perbankan konvensional, itu adalah perisai yang digunakan oleh bank syariah untuk melindungi risiko mereka seperti displaced commercial risk (DCR), withdrawal risk (WR), dan reputation risk. Penelitian Ini menggunakan tinjauan kualitatif tentang dampak positif penggunaan alat pemulusan di lembaga keuangan Islam. Salah satu isu utama yang disoroti adalah sensitivitas bank syariah terhadap perubahan suku bunga konvensional karena banyak produk perbankan syariah yang dibandingkan dengan suku bunga konvensional. Selain itu, keterbatasan teknik dan instrumen yang tersedia untuk memitigasi risiko tingkat pengembalian juga perlu mendapat perhatian serius dari regulator. Sebelum penggunaan alat pemulusan dibatasi oleh BNM, bank syariah diperbolehkan menabung hingga 15% dari perolehan keuntungan. Namun, dalam keadaan tertentu, BNM mengizinkan IB untuk menghemat hingga 30% dari perolehan keuntungan. Oleh karena itu, alat pemulusan seperti PER dan IRR memungkinkan bank syariah menjadi kompetitif dan mengelola risiko unik mereka. Penelitian ini difokuskan pada aspek positif dari penggunaan smoothing tools (STs) dan tidak mencakup aspek negatif dari sudut pandang syari'ah, hukum atau tata kelola perusahaan. Sejak ditinggalkannya alat pemulusan oleh IFI setelah instruksi Bank Negara Malaysia (BNM) pada tahun 2014, tidak banyak perdebatan tentang manfaat penggunaan STs. Oleh karena itu, tulisan ini mungkin memberikan percikan yang diperlukan untuk menyalakan kembali seluruh perdebatan sekali lagi.